Hydrological Hazard: Analysis and Prevention - Tommaso Caloiero (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Due to the considerable impacts of hydrological hazards on water resources, natural environments, and human activities, as well as on human health and safety, climate variability and climate change have become key issues for the research community. In fact, a warmer climate, with its heightened climate variability, will increase the risk of hydrological extreme phenomena, such as droughts and floods. The Special Issue "Hydrological Hazard: Analysis and Prevention" presents a collection of scientific contributions that provides a sample of the state-of-the-art and forefront research in this field. In particular, innovative modelling methods for flood hazards, regional flood, and drought analysis and the use of satellite and climate data for drought analysis were the main research and practice targets that the papers published in this Special Issue aimed to address.